Challenges and opportunities of digital justice in the workplace - Matallana Ruiz, Roberto (2020)
From a legal perspective, the advent of the global pandemic has created new challenges. In the face of the new social tensions that may be generated within this scenario, it is urgent to develop effective and efficient strategies to guarantee effective legal protection without affecting the health and safety of the defendants. Thus, the introduction of Information and Communication Technologies (ICTs) has had a profound impact on the way in which the administration of justice is conceived, so this article examines how this has impacted on the workplace.